ANALYSIS OF ENVIRONMENTAL STATUS OF THE RIVER VOGHJI WITH ARMENIAN INDEX OF WATER QUALITY (Proceedings of the YSU B: Chemical and Biological Sciences, 2016)
Water quality of the Rivers Voghji, Artsvanik and Geghi was evaluated by Armenian Water Quality Index (AWQI) for the first time. It was shown that from the source to the mouth of the river was observed the increase of the value of AWQI that indicates a decline in the water quality of the rivers from the 1st to the 2nd class of pollution. Correlation between the AWQI and other water quality indexes was established.
Keywords: the Voghji River, water quality index, Armenian Water Quality Index, entropy, geo-ecological syntropy